Embedded generation - Jenkins, Nicholas 1954- (Institution of Engineering and Technology, 2000)
This book, intended for both students and practicing engineers, addresses all the issues pertinent to the implementation of embedded generation. Much of the material was originally developed for the UMIST/MSC/CPD course in Electrical Power Engineering so there is a strong tutorial element. However, since this subject is evolving very rapidly, the authors also discuss the technical and commercial consequences of the very high penetration of embedded generation that are to be expected in the years ahead.